A Política Criminal da Guerra às Drogas e a Seletividade Penal no Brasil - Fábio Ricardo Trad Filho (2023)
TRAD FILHO, Fábio Ricardo. The criminal policyofthewarondrugsand penal selectivity in Brazil. 2022. Dissertation (Master of Law) – Faculdade de Direito, Universidade Federal de Mato Grosso do Sul, 2022. This dissertation aims to analyze the so-called “War on Drugs Policy” and observe how this model of criminal policy has impacted and still impacts the Brazilian penal and prison system. Therefore, in the first chapter, it will be necessary to carry out a historical reading of the origins of this policy. Origins going back over a century to the Opium Wars. Still in the initial phase, an observation will be made about the adoption of this model of punitive character in North American soil, and this is necessary insofar as this was the country that outlined the guidelines for this way of dealing with the problem of drug addiction in international scope, which will also be demonstrated and analyzed. Subsequently, the focus of the work will turn to Brazil, since the beginning of the prohibition of substances, still in the Philippine Ordinances. An analysis of drug policy in Brazil will then be carried out, demonstrating, through data, that this model has become more than a failure, a problem, a counterproductive situation that does not end in hyper-incarceration, but, advances and becomes harmful to the entire Brazilian society. Observing that the current model has failed, we will observe two initiatives, which, from the perspective of the concept of Dinamogenesis, may quickly remedy this problem, one in the legislature, PL 399/2015 and another in the judiciary, through the judgment in the STF of RE 635.659/2011. Finally, international examples of more assertive policies will be demonstrated, in line with Human Rights in the matter. The work uses bibliographic, documentary and descriptive methods. Keywords: War on Drugs. Penal Selectivity. Dinamogenesis of War on Drugs.